Physico-mechanical properties of polyethylene reinforced with oil palm fiber composites - Abdul Azim, Hamdan. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The physical and mechanical properties of polyethylene (PE) matrix reinforced with oil palm empty fruit bunch (OPEFB) fiber composites with different by weight loading (10, 15, 20, 25, and 30 wt%) have been studied. Two different types of chemical treatments such as oxidizing agent sodium metaperiodate and coupling agent urea has been used to improve the properties of the composites. Scanning electron micrographs photographs of the fractured and surfaces characteristics were taken to study the fiber/matrix interface adhesion. Reduced fiber agglomeration and improved interfacial was observed under scanning electron microscope in the case of PE reinforced with treated OPEFB fiber and improved the compatibility in the case of urea treated PE reinforced with treated OPEFB fiber composites. Tensile modulus and flexural modulus significantly increased with an increase in fiber loading. However, flexural strength is found decreased beyond 15% by weight fiber loading and tensile strength significantly decreased with an increase in fiber loading. Effect of water absorption on the composites was also observed and it was found that PE reinforced with treated OPEFB fiber composites are less absorbed by water compared with PE reinforced with untreated OPEFB fiber and urea treated PE reinforced with treated OPEFB fibers composites. Overall, chemically treated PE reinforced with OPEFB fiber composites showed better fiber/matrix interactions as observed from the good dispersion of fibers in the matrix system. Compared to the PE reinforced with untreated OPEFB fiber composites, all treated OPEFB fiber reinforced composites had same tendency to slightly increase the mechanical properties of composites.